STRATEGI KOMUNIKASI BIDAN UNTUK MENINGKATKAN PARTISIPASI IBU-IBU MENYUSUI DALAM PROGRAM ASI EKSKLUSIF DI JABON SIDOARJO - Dedi Darmawan; Totok Wahyu Abadi (Kanal: Jurnal Ilmu Komunikasi, 2012)
Government program of exclusive breastfeeding in the last few years shows failure. In the district of Sidoarjo, for example, the level of community participation in exclusive breastfeeding is still relatively low at about 22.8 percent of the announced target of 80 percent. It is interesting to study, therefore this study is aimed to investigate the use of midwives communication strategies to increase the participation of mothers in the exclusive breastfeeding program work in the health center (Puskesmas)in Jabon Sidoarjo. This qualitative descriptive study used snowball sampling techniques with in-depth interviews to key informants and respondents of thirty breastfeeding mothers in Jabon subdistrict of Sidoarjo. The results of this study are that the most dominant communication strategies used by midwives is two-way communication (face to face) with persuasion techniques and methods of redundancy. Midwives barriers consist of internal and external barriers. The internal resistance is reluctance to breastfeed for fear of the breasts are not beautiful anymore, people's understanding on the issue of healthy infants are assessed from the fat physical appearance, and that only a little milk that comes out. While the external resistance is that the babies are not satisfied with only breast milk, reason for working mothers, and the thought of the family, especially the parents, that formula milk is better. The participation rate of breastfeeding mothers is still in the third level, namely level of consultation.